Ultrasonic determination of fatty acids composition in palm oil - Suhardy, Daud; Mustaffa, Nawawi; Farizul Hafiz, Kasim; Saiful Azhar, Saad; Wan Su, Haron (Universiti Sains Malaysia (USM), 2008)
Organized by Universiti Sains Malaysia (USM), 24th - 27th May 2006 at Universiti Sains Malaysia, Penang.